Local Maps of Potential Energy Surfaces and Chemical Pathways. Issue 2 (4th March 2017) - Pietzsch, Annette; Föhlisch, Alexander
Abstract : Potential energy surfaces are a central tool to rationalize, in a multidimensional system, how distortions along defined degrees of freedom link conformation and structural modifications to energy. The local and global mimima define stable conformations and the ground state. Crossings between the ground- and electronically excited-state potential energy surfaces often define rate-limiting steps in chemistry. Here, optically excited or spin-excited states live on different potential energy surfaces. How a molecular wavepacket propagating on a potential energy surface bifurcates at, e.g., a saddle point creates selectivity in a reaction pathway. As a fully quantum mechanical description, wavepacket interference plays an important role. In chemistry, active atomic sites are at the core of excitations, bond creation, and breaking, and thus detailed local information on the potential energy surface surrounding these active atomic centers holds the key to rate and selectivity. The electronic ground state is experimentally elusive to measure, since any measurement determines, at best, modification of the ground state. However, resonant inelastic X-ray scattering (RIXS) has next to electronic and vibronic excitations spectral losses of purely structural excitations [1 ]. Due to the transient strong distortion in the core excited state, vibrational and rotational excitations up to the dissociation limit within the ground-state potential surface become thus observable at selected atomic sites [1 –5 ]. The ensuing vibrational progressions then allow us to reconstruct the underlying local ground-state potential energy surface [6 ]. Subnatural linewidth RIXS also allows selective gating of vibrational excitations, which can be efficiently converted into directional excitation within a molecular frame [7 ]. With this approach of subnatural linewidth RIXS, direct experimental access to potential energy surfaces becomes a reality; in particular, at the active centers and for distortions far from equilibrium that are close to transition and bifurcation points in reactions. Applying this approach of sub-natural line width RIXS to electronically or spin-excitated states will lead to Anti-Stokes spectral signatures [8 ], which additionally give insight into the potential energy surfaces of excited states. Here, sub-natural line width RIXS with transform-limited pulses will open a completely new approach to excited-state dynamics and reaction pathways. The Heisenberg RIXS apparatus at the European XFEL exemplifies this science field.